SnappySonic: An Ultrasound Acquisition Replay Simulator. Issue 1 (30th March 2020) - Thompson, Stephen; Dowrick, Thomas; Xiao, Goufang; Ramalhinho, João; Robu, Maria; Ahmad, Mian; Taylor, Dan; Clarkson, Matthew J.
SnappySonic provides an ultrasound acquisition replay simulator designed for public engagement and training. It provides a simple interface to allow users to experience ultrasound acquisition without the need for specialist hardware or acoustically compatible phantoms. The software is implemented in Python, built on top of a set of open source Python modules targeted at surgical innovation. The library has high potential for reuse, most obviously for those who want to simulate ultrasound acquisition, but it could also be used as a user interface for displaying high dimensional images or video data.